Knowledge and Awareness on Antibiotic Resistance Among the Residents of Barangay San Fabian, Echague, Isabela - Edmelyn Babas Cacayan; Angelito Estoesta Alvarado; Marvin Antonio Miguel; Jennifer Ramos Montalban; Shiela Escobido Mayo; Claudine Estuesta Medina; Shaina Antonio Medina (Health Notions, 2022)
The emergence of antibiotic resistance continues to threaten the health of the people. It becomes serious for it causes infections difficult to treat as they unconsciously acquiring antibiotic resistance by consuming antibiotic containing products, inappropriate use and abusing this drug. Knowledge and awareness are huge factors in contributing to the present problem. The purpose of this study is to determine the level of knowledge and awareness of the residents of barangay San Fabian, Echague, Isabela regarding antibiotic resistance. This quantitative research used descriptive research design, specifically descriptive-survey method to assess the level of knowledge and awareness of the respondents regarding antibiotic resistance and it also aims to know the extent to which how these components are influenced by their age, gender and highest educational attainment. A researcher-made questionnaire was utilized as the main instrument in gathering the data needed in this study, it underwent pilot test and was reviewed and evaluated using Cronbach's alpha tool for validity. The questionnaire was distributed to the respondents that was selected using convenience sampling and snowball sampling technique. Based on the evidence presented, the age bracket with the highest level of knowledge regarding antibiotic resistance is 18-35 years old with a weighted mean of 3.62. It also showed in statistical data that males are more knowledgeable with a mean of 3.51, than females with a mean of 3.39. The educational attainment with highest level of knowledge is vocational graduate with a weighted mean of 3.50. For the level of awareness, age bracket 18-35 years old has the highest mean which is 3.71, the males also have a higher awareness regarding antibiotic resistance with a mean of 3.65, and vocational graduate has the highest level of awareness with a mean of 3.88. The Chi square test revealed that there is no significant relationship between the level of knowledge and level of awareness on antibiotic resistance and the respondents age, gender, and highest educational attainment. A program was proposed to help raise awareness and promote health education in the community regarding antibiotic resistance.  The findings in this study will serve as a standard to maintain and improve the quality of health care services in the barangay and for nursing education to improve clinical practice. Keywords: antibiotic resistance; knowledge; awareness